(untitled) (Journal of Engineering, 2019)
Tests were performed on Marshall samples and were implemented for permanent deformation and resilient modulus (Mr) under indirect tensile repeated loading (ITRL), with constant stress level. Two types of liquid asphalt (cutback and emulsion) were tried as recycling agents, aged materials that were reclaimed from field (100% RAP), samples were prepared from the aged mixture, and two types of liquid asphalt (cutback and emulsion) with a weight content of 0.5% were utilized to prepare a recycled mixture. A group of twelve samples was prepared for each mixture; six samples were tested directly for ITRL test (three samples at 25˚C and three samples at 40˚C), an average value for ITRL for every three samples was calculated (ITRL for unconditioned samples). The other six samples were placed in volumetric flask 4000-ml heavy- wall glass filled with water at 25˚C under a vacuum pressure of (3.74 kPa) for 5 to 10 minutes. Then the samples were put in deep freeze for 16 hours at -18˚C. The samples were frozen then were transported to a water bath at 60ºC for 24 hours. Then they were soaked in a water bath for 1 hour at 25ºC and tested for the ITRL test (three samples at 25˚C and three samples at 40˚C), the average value of ITRL for every three samples was calculated (ITRL for conditioned samples). It was concluded that the reduction in (Mr) at the Conditioned test as compared to the Unconditioned test was (29.5%, 22.27% and 9.09%) at 25˚C, while at 40˚C, the reduction was (21.28%, 15.53%, and 17.89%) for aged and recycled mixtures with (cutback), and (emulsion) respectively. The change in permanent deformation at the Conditioned test as compared to Unconditioned one was (76.19%, 75.61% and 53.22%) at 25˚C, while at 40˚C it was (56.48%, 35.19%, and 78.33%) for aged and recycled mixtures with (cutback), and (emulsion) respectively.